2005
DOI: 10.1093/occmed/kqi088
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholinesterase level of Ethiopian farm workers exposed to chemical pesticide

Abstract: The sprayers in both farms were the most affected groups, suggesting that improved controls on workplace exposure to pesticide is required in these groups of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…This observation supports earlier reports (25,26). Exposure to OP pesticides exerts toxic effect by inhibiting enzymatic degradation of neurotransmitter; acetylcholine which results inaccumulation of acetylcholine, continued excitation of the neurons, paralysis, respiratory failure or death (27).…”
Section: Discussionsupporting
confidence: 90%
“…This observation supports earlier reports (25,26). Exposure to OP pesticides exerts toxic effect by inhibiting enzymatic degradation of neurotransmitter; acetylcholine which results inaccumulation of acetylcholine, continued excitation of the neurons, paralysis, respiratory failure or death (27).…”
Section: Discussionsupporting
confidence: 90%
“…While spraying pesticides, the use of PPE could reduce their direct contact with skin, and inhalation of pesticides, thereby, potentially reducing acute and chronic health hazards of pesticides for the sprayers (13). These results are quite consistent with previous studies conducted in Ethiopia and they have also shown that; the handling and storage of chemical pesticides, personal hygiene and the proper use of personal protective equipment by farm-workers are below standard (13,14). A recent study also found that only a few workers use some sort of PPE, and most do not take a shower after pesticide application (12).…”
Section: Discussionsupporting
confidence: 87%
“…Organophosphates and carbamates are the predominant types of pesticide used and are of specific concern due to their highly toxic impact on humans and other organisms 3,4) . Exposure to organophosphate and carbamate pesticides is the major cause of cholinesterase depression and plasma cholinesterase has been used as an exposure index, to assess low-level, chronic residue exposures among field workers [5][6][7] . Although agrichemicals are important for food hygiene, by preventing mould damage, flies, and other insects from contaminating food, their potential hazardous effects on humans makes their inappropriate use worrisome 8) .…”
mentioning
confidence: 99%